Applications of pulsed gradient spin-echo NMR diffusion measurements to solution dynamics and organization - Price, William S. (Diffusion Fundamentals, 2005)
The study of solution dynamics is a very fundamental area of research with wide ranging importance from physical chemistry through to the life sciences. A common theme is that the interactions which control the dynamics and organization of solutions are generally very weak. Translational diffusion provides a non-invasive, direct and natural probe of the dynamics and pulsed gradient spin-echo (PGSE) NMR is a convenient means of measuring diffusion. This paper gives a brief introduction to translational diffusion as a probe of solution dynamics and of the PGSE NMR method before presenting some representative examples illustrating the power of diffusion measurements for elucidating the molecular behaviour. The use of PGSE NMR to study solution dynamics and organization is a very active area of research and a very large literature already exists, consequently, the coverage of possible applications and the literature cited here is not comprehensive.